Measuring natural rate of interest in Uzbekistan - Islomjon Inkhomiddinov (Graduate Institute of International and Development Studies, 2025)
The natural rate of interest, often interpreted as the equilibrium real interest rate, serves as a critical benchmark for evaluating the stance of monetary policy. This paper investigates the natural rate of interest in Uzbekistan using three econometric approaches: the HLW-type model1 , a modified HLW-type model, and the Central Bank of Uzbekistan's Quarterly Projection Model (QPM), semi-structural framework. The semi-structural HLW-type and modified HLW-type models estimate the real interest rate using core inflation, while the QPM relies on headline inflation. The results indicate that the natural rate was relatively stable across the models. The semi-structural HLW-type and modified HLW-type models produced average natural rate estimates of 4.5 percent and 4.1 percent, respectively, while the QPM estimated a slightly lower average rate of 3.4 percent. On average, the natural rate across all models was approximately 4.0 percent. In contrast, the real interest rate exhibited significant variability, reflecting periods of accommodative monetary policy before the adoption of the inflation targeting regime and restrictive policies during the IT regime's active implementation. These findings emphasize the critical role of accurately estimating the natural rate to guide monetary policy and ensure macroeconomic stability effectively.
Keywords: E42; E43; E52; E59; 330; Natural level of Real Interest Rate; Core Inflation; Kalman Filter; Bayesian Estimation